Design and fabrication of a student competition based racing car - Abdul Aziz, Faieza; Salit, Mohd Sapuan; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Supeni, Eris Elianddy (Academic Journals, 2009)
Design, fabrication and testing of a student competition based racing car are presented in this paper. The competition will encourage students to compete and demonstrate their practical abilities to develop a mini race car. The design guideline is based on the specifications set by the organizer, Universiti Teknikal Malaysia (UTeM) Formula Varsity Car, 2008. Design of the car was carried out using CATIA solid modelling system. The car was fabricated in one of the laboratory in mechanical and manufacturing engineering, Universiti Putra Malaysia. The car has been tested for its performance. Two types of test were conducted which were Static Test and Track Test.